2020
DOI: 10.3389/fonc.2020.00073
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Cancer and Dementia: A National Cohort Study in Sweden

Abstract: Background: Previous studies have found that the incidence of dementia is lower in patients with cancer. However, the impact of survival bias, as well as the confounding by medical treatment, have not been fully addressed. We aimed to explore the subsequent risk of dementia in different follow-up intervals among patients with cancer, as well as the risk before the diagnosis of cancer.Methods: By using the Swedish Cancer Register and the Swedish Hospital Discharge Register, we systematically examined the risk o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 37 publications
2
30
2
Order By: Relevance
“…Our search returned 2764 unique records; 22 studies (19 cohort studies and 3 case-control studies) met the eligibility criteria and were included (eFigure 1 in the Supplement ). In total, 13 studies 10 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 investigated all cancer types (eTable 2 in the Supplement ); 5 studies 49 , 50 , 51 , 52 , 53 investigated prostate cancer; 3 studies 9 , 54 , 55 investigated NMSC; and 1 study 56 investigated breast cancer ( Table 1 ). Five studies that investigated all cancer types (5 of 13) additionally reported cancer type–specific subgroup analyses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our search returned 2764 unique records; 22 studies (19 cohort studies and 3 case-control studies) met the eligibility criteria and were included (eFigure 1 in the Supplement ). In total, 13 studies 10 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 investigated all cancer types (eTable 2 in the Supplement ); 5 studies 49 , 50 , 51 , 52 , 53 investigated prostate cancer; 3 studies 9 , 54 , 55 investigated NMSC; and 1 study 56 investigated breast cancer ( Table 1 ). Five studies that investigated all cancer types (5 of 13) additionally reported cancer type–specific subgroup analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies 41,42,46 included in this review presented time-varying HRs, but evidence from these reports is inconclusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some limitations exist, most notable being the limited number of cancer cases, particularly of those diagnosed with both incident cancer and dementia (6.3%). Although this is indicative of the protective role that cancer appears to play in dementia risk, it impeded further investigations into the potential differential impact of specific cancer types on risk as well as a more sophisticate multi‐state model (ie, including incident cancer diagnosis as a separate state) 8,22,35,36 . Information on cancer stage was also not available; due to the influence of cancer stage on reductions in survival, stratification by cancer stage could have permitted a further in‐depth investigation into survival bias.…”
Section: Discussionmentioning
confidence: 99%
“…Although this is indicative of the protective role that cancer appears to play in dementia risk, it impeded further investigations into the potential differential impact of specific cancer types on risk as well as a more sophisticate multi‐state model (ie, including incident cancer diagnosis as a separate state). 8 , 22 , 35 , 36 Information on cancer stage was also not available; due to the influence of cancer stage on reductions in survival, stratification by cancer stage could have permitted a further in‐depth investigation into survival bias. However, in a national cohort study on US veterans, adjustment for cancer severity was not found to impact results in previous studies.…”
Section: Discussionmentioning
confidence: 99%